The Impact of Culturally Responsive Leadership Traits on Alabama K-12 Teachers’ Intention to Leave and Job Satisfaction - Baker, Samuel; Epstein, Michael; Rabas, Audrey; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2024)
Previous research has shown that culturally responsive leadership leads to improvements in teachers’ performance and job satisfaction. The goal of the current research study is to examine if there is a linear relationship between the Alabama state high school teachers’ perception of their school principals’ Culturally Responsive Leadership Traits upon the dependent variables of job satisfaction and turnover intention. Based on a sample of 95 Alabama state high school teachers, the key findings of this research study showed that school principals’ providing professional development had a marginally statistically significant negative linear relationship with school teacher self-reported total job satisfaction along with the statistically significant relationship between the increasing level of a school teacher’s intention to leave their job due to the increasing amounts instructional resources that are being offered to them by their school principals. In contrast, fostering the Culturally Responsive Leadership Trait of Maximizing the Instruction Time for subordinate teachers by school principals in the state of Alabama can be a cornerstone to build upon for future school principals’ professional development to further improve job satisfaction among their subordinate Alabama K-12 school teachers.